2015
DOI: 10.3390/agriculture5030538
|View full text |Cite
|
Sign up to set email alerts
|

Transferability of Models for Estimating Paddy Rice Biomass from Spatial Plant Height Data

Abstract: It is known that plant height is a suitable parameter for estimating crop biomass. The aim of this study was to confirm the validity of spatial plant height data, which is derived from terrestrial laser scanning (TLS), as a non-destructive estimator for biomass of paddy rice on the field scale. Beyond that, the spatial and temporal transferability of established biomass regression models were investigated to prove the robustness of the method and evaluate the suitability of linear and exponential functions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 57 publications
7
43
0
2
Order By: Relevance
“…The study area was then extracted from the registered data and exported as an ASCII file containing XYZ coordinates and the timestamp per point for further point density reduction. This workflow is similar to Tilly et al [38,49,50].…”
Section: Registering Multitemporal Tls Datamentioning
confidence: 80%
See 3 more Smart Citations
“…The study area was then extracted from the registered data and exported as an ASCII file containing XYZ coordinates and the timestamp per point for further point density reduction. This workflow is similar to Tilly et al [38,49,50].…”
Section: Registering Multitemporal Tls Datamentioning
confidence: 80%
“…Eitel et al [40] noted the necessity of multiple ATLS when monitoring highly dynamic 3D ecosystem processes changing on a minute or hourly basis. A set-up of multiple TLS systems was employed by Tilly et al [38]. The level of accuracy reached in our studies can be obtained when using one single static position at a height of 3.6 m. For CHM accuracy the measurement set-up should be at least 3.6 m for crops reaching a maximum height of approximately 2.8 m, as shown.…”
Section: Study Area and Measurement Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Both soils had a relatively similar height in the second month of measurements, but in the third month of the study the plant height for the sandy loam soil increased significantly to about 10 cm higher than for the loamy sand soil. A study by Tilly et al (2015) showed that plant height had a very strong relation to biomass production of rice (R 2 : 0.72 to 0.91) and recommended the variable as a non-destructive estimator for biomass of paddy rice. In particular, the plant height influenced the aboveground biomass significantly as reported by Lou et al (2016), while this biomass could be responsible for evapotranspiration, therefore the plant height presented in Table 2 might explain the variations in soil water loss between two study soils.…”
Section: Resultsmentioning
confidence: 99%